The Electone in Music Education at the Vietnam National Academy of Music - Thi Quynh, Le (VNU Journal of Science: Education Research; Vol 41 No 3, 2025)
The Electone, an electronic keyboard instrument, was introduced into the curriculum of the Vietnam National Academy of Music (VNAM) in the early 1990s. By leveraging advanced electronic technology and engaging both hands and feets during performance, the instrument functions as a “miniature orchestra” with virtually unlimited creative potential. The near-total absence of research on musical instruments in Vietnam has hindered the development of Electone training.  This article presents basic research that is interconnected, systematizing and integrating fragmented knowledge into a comprehensive picture of the instrument’s developmental trajectory, thereby establishing a solid academic foundation and a shared body of knowledge to support professional training.